2018
DOI: 10.1371/journal.pone.0200686
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of whole body CT scanning in patients with unexplained weight loss

Abstract: BackgroundUnexplained weight loss is a non-specific complaint with myriad potential etiologies. Increasingly, whole body CT studies are being performed in patients with unexplained weight loss to exclude organic etiologies such as malignancy. Our study aims to assess the diagnostic accuracy and yield of whole body CT in these patients.Methods and materialsPatients who had a whole body CT scan for investigation of unexplained weight loss as their primary complaint from 2009–2012 were retrospectively reviewed. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
10
3
Order By: Relevance
“…Our findings differ somewhat from a previously published study by Goh et al 3 . on the role of whole‐body CT in the work up of unexplained weight loss.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings differ somewhat from a previously published study by Goh et al 3 . on the role of whole‐body CT in the work up of unexplained weight loss.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings differ somewhat from a previously published study by Goh et al 3 on the role of whole-body CT in the work up of unexplained weight loss. Goh's study of 301 patients in a different population group found that CT had a diagnostic yield of 33.5% in patients with unintentional weight loss, higher than in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although weight loss was not the primary reason to perform a scanner in Damiano's study, it was the only significant difference between the tumorbearers (-6.9±5.8 kg) and the others (-3.8±4.5 kg). Higher rates of cancers (28% to 36%) were reported in radiologic series using a CTscanner in patients with unexplained weight loss, not selected for uncontrolled diabetes [9,19], probably due to additional localizing symptoms, anemia and elevated tumor markers in these series. The detection of a deep cancer on 6.1% of CT-Scanners shows that this exam should be considered in subjects with uncontrolled diabetes and an unexpected weight loss.…”
Section: Discussionmentioning
confidence: 61%